Day 3 Wed, April 26, 2017 2017
DOI: 10.2118/188046-ms
|View full text |Cite
|
Sign up to set email alerts
|

NanoSurfactant for EOR in Carbonate Reservoirs

Abstract: A new class of surfactants for enhanced oil recovery (EOR) applications has been developed in the form of petroleum sulfonate salt nanoparticle dispersions in seawater. These NanoSuractants (NS) are 10- to 60-nm particles of the seawater-insoluble petroleum sulfonate salts, one of the most abundant and inexpensive industrial surfactants, that are resiliently stable in seawater at elevated temperatures via a special class of co-surfactants. They can be easily prepared in the field by mixing with seawater at amb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 5 publications
0
9
0
Order By: Relevance
“…We first investigated the colloidal stability of Pure Sulf and Sulf+Coca formulations in deionized water and high salinity water (see the Experimental Section in Materials and Methods for the notations of the formulations). As has been identified, Pure Sulf solutions were unstable in high salinity water and precipitated immediately after preparation. Figure shows the DLS measurements of Pure Sulf oil-swollen micelles in deionized water, Sulf+Coca oil-swollen micelles in deionized water, and Sulf+Coca oil-swollen micelles in high salinity water. As shown, Pure Sulf solution has the highest polydispersity with their measured hydrodynamic diameters ranged from 10 to 400 nm.…”
Section: Resultsmentioning
confidence: 88%
See 2 more Smart Citations
“…We first investigated the colloidal stability of Pure Sulf and Sulf+Coca formulations in deionized water and high salinity water (see the Experimental Section in Materials and Methods for the notations of the formulations). As has been identified, Pure Sulf solutions were unstable in high salinity water and precipitated immediately after preparation. Figure shows the DLS measurements of Pure Sulf oil-swollen micelles in deionized water, Sulf+Coca oil-swollen micelles in deionized water, and Sulf+Coca oil-swollen micelles in high salinity water. As shown, Pure Sulf solution has the highest polydispersity with their measured hydrodynamic diameters ranged from 10 to 400 nm.…”
Section: Resultsmentioning
confidence: 88%
“…Two surfactant formulations were prepared: (i) “Pure Sulf” oil-swollen micelles with 0.1 wt % chemicals (95 wt % Sulf and 5 wt % Deca within the chemicals) and (ii) “Sulf+Coca” oil-swollen micelles with 0.2 wt % chemicals (43.2 wt % Sulf, 54.5 wt % Coca, and 2.3 wt % Deca within the chemicals). The particular compositions were chosen based on prior studies optimized for enhanced oil recovery operations. Both formulations were prepared in deionized water or high salinity water for consecutive characterization experiments. Note for the formulations in high salinity water surfactants were first mixed in deionized water at higher concentration and then the high salinity water was added to reach the desired concentrations.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Regardless of the adopted classification and division of secondary methods to support oil production, each case should be considered individually. Many examples can be found in the literature from laboratory tests through to computer simulations and test pilots, ending with the analysis of completed projects in specific fields [13][14][15][16][17][18][19]. The full cycle of preparation and implementation of an EOR project, from laboratory research to its implementation in an oil field and confirming its effectiveness, is typically complex, long-lasting and, thus, expensive.…”
Section: Introductionmentioning
confidence: 99%
“…The entry of engineering into the nanoscale has opened up many new areas previously inaccessible without the use of nanotechnology, as well as the possibility of modifying existing technological solutions (e.g., EOR processes). Examples of research projects or nanotechnology-based solutions have been cited repeatedly [8,14,16,[20][21][22][23][24][25][26]. These studies have shown that during EOR processes, rock wettability is particularly important in carbonate rocks.…”
Section: Introductionmentioning
confidence: 99%